OBSERVATIONS ON THE INTERVENTION OF NATO IN KOSOVO - Cristian Jura, Cristian Jura (Agora International Journal of Juridical Sciences, 2013)
On the date of June 12th 1998, the North-Atlantic Council, gathered on the level of theministers of defense, required the evaluation of the possible additional measures which NATOcould take under the conditions of aggravation of the crisis from Kosovo. Consequently, onthe date of October 13th 1998, pursuant to the aggravation of the situation, the North-AtlanticCouncil authorized orders of activation for the air attacks. This measure is meant to supportthe diplomatic efforts in order to determine the regime of MiloÅŸevici to withdraw the forcesfrom Kosovo, to cooperate for the end of violence and to facilitate the return of refugees totheir homes. However, in the last moment, pursuant to other diplomatic initiatives of theofficials of NATO and United States, the president MiloÅŸevici accepted to collaborate, and theair attacks were cancelled